2000
DOI: 10.1023/a:1005498402659
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We investigated the effects of the calcium-channel blocker verapamil hydrochloride on the production of cytokine-induced neutrophil chemoattractant (CINC) following reperfusion injury in rat liver. Ischemia was induced for 30 min by portal vein occlusion. Animals were pretreated with intravenous injection of verapamil hydrochloride (2.5 mg/kg) 5 min before vascular clamp. Verapamil hydrochloride limited increases in the chemoattractant compared with nonpretreated rats. Most cells immunostained for chemoattract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…Kupffer Cells are resident liver macrophages and have been shown to be activated early following IR injury [ 92 , 93 ]. However experiments blocking macrophage activity have had varied results with some studies demonstrating that Kupffer cell blockade or modulation attenuated IR injury [ 94 , 95 ] whilst other models have shown increased IR injury following Kupffer cell depletion [ 96 ].…”
Section: Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kupffer Cells are resident liver macrophages and have been shown to be activated early following IR injury [ 92 , 93 ]. However experiments blocking macrophage activity have had varied results with some studies demonstrating that Kupffer cell blockade or modulation attenuated IR injury [ 94 , 95 ] whilst other models have shown increased IR injury following Kupffer cell depletion [ 96 ].…”
Section: Macrophagesmentioning
confidence: 99%
“…Treatment of mice with recombinant IL-10 prior to IR injury significantly attenuated IR injury and interestingly was associated with a reduction in TNFα production in the liver [ 105 ]. IL-10 depletion has been shown to result in increased liver injury and increased production of TNFα and IL-6 (89) [ 95 ] again demonstrating an interplay between these pro-inflammatory and anti-inflammatory cytokines and suggesting that manipulating cytokine production could alter IR injury. The effect of IPC on IL-10 levels post IR injury have been conflicting.…”
Section: Cytokinesmentioning
confidence: 99%
“…Although the participation of XOR in WBS has not been reported yet; however, other connective tissue diseases, such as Loeys-Dietz and Marfan syndromes, are associated with increased XOR protein levels in aortic samples [ 16 , 17 ]. Interestingly, ROS generated by hypoxanthine and xanthine oxidase can be inhibited by curcumin (CUR) [ 18 ] as well as verapamil hydrochloride (VER) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the participation of XOR in WBS is unknown, related diseases as Loeys-Dietz and Marfan syndromes showed XOR protein levels increased in aortic samples (Soto et al, 2020; Rodríguez-Rovira et al, 2022). Previous studies have reported that ROS generated by hypoxanthine and xanthine oxidase were inhibited by curcumin (Akter et al, 2020) and the calcium channel blocker verapamil hydrochloride (Liang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%